Alma Ata: experiencias que validan sus propuestas 40 años después, para proyectarlas al futuro - Carbone Campoverde, Fernando (2019)
Much has been discussed about why after the International Conference of health of Alma Ata of 1978 has not followed a momentum that made possible its implementation and more health goes by not only different but opposite currents in some cases. While it is true that this discussion is important to better understand the lessons learned around the so-called primary health care, avoid errors and deepen its achievements, it is more important to operate, in the sense that Alma Ata proposed: comprehensive and inclusive health models that reflect justice, equity, innovation and boldness needed to build a better, more just, healthy, developed and happy world. In the Americas there are relatively recent experience advocating for it, that it is important to present initially, since they are still in the process of systematization and research.